NEGOSIASI MUKA DALAM KOMUNIKASI ANTARBUDAYA MASYARAKAT TRANSMIGRAN (JAWA) DAN PENDUDUK LOKAL (MELAYU) DI DESA KUALA KILAN KECAMATAN BATANG CENAKU KABUPATEN INDRAGIRI HULU RIAU - Nur, Veni Widyasti; ", Yasir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Intercultural communication especially the way a person face negotiates in an environment with cultural differences is an interesting phenomenon in the midst of the people of Kuala Kilan Village. People from different cultures have their own way of looking at the identities of others. So, face negotiations and adjustments are needed so that the two cultures can unite and can know the need for faces to be displayed in a social environment. The purpose of this study is to determine self-identity, conflict management and the impact of cultural behavior in intercultural communication between Javanese transmigrants and Malay local residents in the Kuala Kilan Village Batang Cenaku District Indragiri Hulu Regency Riau.This study uses a descriptive qualitative approach. This research uses face negotiation theory. This research was carried out in Kuala Kilan Village, Batang Cenaku District, Indragiri Hulu Regency, Riau. The reason for choosing a location in Kuala Kilan Village, Batang Cenaku Subdistrict is to find out whether the relationship between the transmigrant (Javanese) community and the local population (Malay) runs harmoniously or if there are conflicts or obstacles that occur. The withdrawal of informants from this study was determined using the Purposive technique. Collection techniques in this study were carried out through observation, interviews, and documentation.The results of this study indicate that the face negotiations that occur between Javanese transmigrants and their local Malay residents manage the faces or identities that they will display to maintain their dignity in the social environment. They manage intercultural communication conflicts by accepting, combining, appreciating, respecting, learning each other's opposing cultures and positive attitudes that are adapted to situations and conditions to resolve existing problems between Javanese migrants and local Malays. Therefore, the actions that are displayed through cultural behavior between Javanese transmigrants and their local Malay population can adapt well and mutual tolerance. The results of research conducted by researchers that in the village of Kuala Kilan between the people of the village of Kuala Kilan they can negotiate their self-image or self-identity. and Javanese societies have adapted, accepted the differences, united the two cultures, the two tribes live in harmony, respect each other and can coexist. Keywords: Face Negotiation, Intercultural Communication, Javanese Society, Malay Society.